2008 International Conference on Signals and Electronic Systems 2008
DOI: 10.1109/icses.2008.4673424
|View full text |Cite
|
Sign up to set email alerts
|

Improved electrothermal model of the thermoelectric generator implemented in SPICE

Abstract: In the paper an improved model of the thermoelectric generator (TEG) is shown. The electrothermal model was implemented into electronic circuits simulator SPICE and it was used during simulation of energy harvesting processes. In the latest version a dependence of the internal electrical resistance of the Peltier module in respect to temperature changes was introduced. Therefore, better accuracy of the model was achieved especially for small gradients of temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Up to the moment the current paper was written, no SPICE models employing the parasitic components were found by the authors. The existent models [10][11][12][13][14][15][16] only take into account the internal resistance, Seebeck coefficient and thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Up to the moment the current paper was written, no SPICE models employing the parasitic components were found by the authors. The existent models [10][11][12][13][14][15][16] only take into account the internal resistance, Seebeck coefficient and thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…For some years the authors have dealt with thermogenerators based on Peltier modules that could harvest waste industrial heat and convert it into electrical energy that is next used to supply nodes of wireless sensor networks (WSN) [3,4]. In thermoelectric generators the output voltage is approximately proportional to the temperature gradient but its level is mostly not sufficient to be directly used to supply sensor nodes.…”
Section: Introductionmentioning
confidence: 99%
“…It was next transformed to a model of TEG [6] that is still under study and subjected to further modifications and improvements. Some other concepts of simulations models of TEGs were worked out by other research teams and can be found in [7] and [8].…”
Section: Introductionmentioning
confidence: 99%